METHODOLOGICAL ASPECTS OF TEACHING "EMERGENCY MEDICINE" TO STUDENTS OF DENTAL FACULTY - O.B. Yaremenko; D.V. Dobriansky; P.F. Dudkina; R.I. Ilnytskyi; I.P. Tarchenko; N.M. Reznikova (Проблеми екології та медицини)
Learning the discipline "Emergency medicine" provides familiarization of students with the basic principles of emergency service and mastering the professionally oriented skills and abilities. Lack of knowledge and low motivation of dental students to learning the non-core subjects requires from teachers to use the interactive teaching methods, primarily focused on increasing motivation and incentives to work independently. Therefore, in teaching the discipline «Emergency medicine» one should include a variety of learning methods that facilitate efficient mastering of new knowledge. The staff of Internal Medicine Department of Dental Faculty uses professional-oriented business games, talks, discussion of clinical situations and situational problems, competitions of scientific works / reports and provides personalized evaluation of students in time of practical training during practical sessions.